2021
DOI: 10.3390/nu13020689
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Intake and Incidence of Diabetes Complications in Elderly Patients with Type 2 Diabetes—Analysis of Data from the Japanese Elderly Diabetes Intervention Study (J-EDIT)

Abstract: This study investigates the associations between sodium intake and diabetes complications in a nationwide cohort of elderly Japanese patients with type 2 diabetes aged 65–85. Data from 912 individuals regarding their dietary intake at baseline is analyzed and assessed by the Food Frequency Questionnaire based on food groups. Primary outcomes are times to diabetic retinopathy, overt nephropathy, cardiovascular disease (CVD), and all-cause mortality during six years. We find that mean sodium intake in quartiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Most observational studies measured the dietary intake using standard dietary methods such as 24 h recall (n = 4) [ 20 , 34 , 35 ], food frequency questionnaires (FFQ) (n = 23) [ 12 , 18 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], or 3-day food records (n = 3) [ 17 , 51 , 52 ]. A general-based interviewer-administered questionnaire was administered in 20 observational studies, and only one study evaluated dietary sodium intake from urinary excretion levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most observational studies measured the dietary intake using standard dietary methods such as 24 h recall (n = 4) [ 20 , 34 , 35 ], food frequency questionnaires (FFQ) (n = 23) [ 12 , 18 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], or 3-day food records (n = 3) [ 17 , 51 , 52 ]. A general-based interviewer-administered questionnaire was administered in 20 observational studies, and only one study evaluated dietary sodium intake from urinary excretion levels.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of a prospective study by Horikawa and associates indicated that, among patients who consumed less than an average of 268.7g of vegetables, high sodium intake was associated with a higher incidence of DR in elderly patients with type 2 diabetes (The results of third [4.4g/d], and fourth [5.9g/d] quartiles compared with the first quartile [2.5g/d], HRs were 2.61 [1.00–6.83], and 3.70 [1.37–10.02], respectively, p = 0.010) [ 37 ]. Another prospective study by Roy and colleagues reported increased sodium intake as a risk factor for DME progression (Q4 vs. Q1, OR: 1.43, 95%CI: 1.10–1.86, p = 0.008), but there was no significant association with DR. [ 49 ] The evidence provided by the remaining studies showed no association of sodium intake with DR [ 47 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, epidemiological studies, which search for associations between food consumption and DM, are limited. 4 By contrast, eating standards based on the consumption of ultraprocessed foods and the greater intake of fresh fruits and vegetables has proven to be effective in both the prevention and management of chronic non-communicable diseases (NCDs). 5 This diet standard, known as "Mediterranean", is gaining ground, as it promotes healthy lifestyles and a high regard for seasonal foods.…”
mentioning
confidence: 99%
“…7 However, epidemiological studies about food consumption are scarce in the literature, and their results are often highly inconsistent. 4,8 One of the challenges to conduct these studies in Brazil is the large territorial size of the country, associated with the population's heterogeneity, as well as its differences in culture and regional eating habits. Some studies are based on data compiled by specific research projects, such as the Household Budget Survey (HBS), the National Diet and Nutrition Survey, and the Surveillance System of Risk and Protection Factors for Chronic Diseases by Telephone Inquiry (VIGITEL).…”
mentioning
confidence: 99%
See 1 more Smart Citation